The Use of Artificial Intelligence (AI) and Artificial Intelligence (AI) in Islamic Banking and Investment for Sustainable Economic Development - Khoso, Prof. Dr. Aijaz Ali; Pathan , Dr. Muhammad Shoaib Khan (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
This considers the utilization of fake insights (AI) in Islamic contributing. AI innovation is exceptionally well known among conventional banks and Islamic banks, which is obvious within the commitment of AI to Islamic ventures. This innovation permits financial specialists to analyze their stocks based on their stock cost, the position of each stock, and future prices based on stock costs and data. The consideration could be a conceptual discourse on the utilization of AI in Islamic contributing, centering on the part of bots in mining, algorithmic trading, stock buying and contributing, counting robo-advisors, robo-Islamic advisors (RIAs), and robo-financial advisors (RFAs) operating within the Islamic venture show. The conference centered on the application of information and compliance within the venture and money-related administration businesses. The results of this study are given in a diagram of the impacts, confinements, and future investigation.